Enabling and Inhibiting Factors of the Continuous Use of Mobile Short Video APP: Satisfaction and Fatigue as Mediating Variables Respectively - Huang L; Dong X; Yuan H; Wang L (Psychology Research and Behavior Management, 2023)
Lu Huang,* Xiuli Dong, Hang Yuan, Lihua Wang* Business School of Sichuan University, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lihua Wang, Business School of Sichuan University, Chengdu, Sichuan, People’s Republic of China, Tel +86 +28-85415451, Fax +86 +28-85418379, Email 2470610738@qq.comPurpose: The short video APP has entered the stage of competition for stock, making it crucial to keep users engaged in their APP to promote continuous usage. Previous studies on the continuous use intention of mobile short video APP were relatively limited, with most studies focusing only on promoting factors. Therefore, based on the dual-factor theory of “enabling-inhibiting”, and drawing on the Information System Continuance Model (ECM-ISC) and Cognitive Load Theory, this study extracted two variables, satisfaction and fatigue, to construct an integrated model to explore their enabling and inhibiting effects on continuous use intention.Methods: This study selected TikTok APP users as the respondents, obtained 681 valid questionnaires and analyzed with structural equation modeling (SEM) using SPSS24.0 and Amos23.0 software.Findings: The study investigated the factors that influence users’ continuous use intention of short video APP. It shows that in enabling mechanism, perceived usefulness and social influence will increase user satisfaction and thus promote their continuous use intention, and perceived playfulness has a direct effect on the continuous use intention. In inhibiting mechanism, information overload and communication overload are positively correlated with emotional fatigue, which further reduces the continuous use intention.Contribution/Conclusion: Based on the dual-factor theory of “enabling-inhibiting”, the study established an integration model to more comprehensively reveal the impact mechanism of short video APP users’ continuous use intention. The study found that the fatigue caused by information and communication overload can inhibit users’ continuous use intention of short video APP. Therefore, to improve users’ continuous use intention, short video APP should not only increase users’ satisfaction but also reduce the fatigue caused by overload.Keywords: short video APP, continuous use intention, satisfaction and fatigue, enablers, inhibitors, ECM-ISC model